Back Cover: Preparation of Magnesium, Cobalt and Nickel Ferrite Nanoparticles from Metal Oxides using Deep Eutectic Solvents (Chem. Eur. J. 37/2016). Issue 37 (16th August 2016) - Söldner, Anika; Zach, Julia; Iwanow, Melanie; Gärtner, Tobias; Schlosser, Marc; Pfitzner, Arno; König, Burkhard
Abstract : Deep eutectic solvents based on natural compounds dissolve simple metal oxides and were used as reaction media to synthesize spinel‐type ferrite nanoparticles MFe2 O4 (M=Mg, Zn, Co, Ni). By employing deep eutectic solvents, the reactions proceed at much lower temperatures than the respective solid‐phase reaction of the metal oxides and at the same temperatures as syntheses with comparable calcination processes using metal salts. More information can be found in the Full Paper by B. König et al. onpage 13108 ff.